2014
DOI: 10.1007/s40258-014-0085-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Early Versus Late Systemic Lupus Erythematosus Diagnosis on Clinical and Economic Outcomes

Abstract: Patients diagnosed with SLE sooner may experience lower flare rates, less healthcare utilization, and lower costs from a commercially insured population perspective. This finding needs to be further explored within the context of background SLE disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 20 publications
1
77
1
2
Order By: Relevance
“…A higher percentage of cases than controls was treated with corticosteroids or anti-rheumatic medications (methotrexate and hydroxychloroquine), consistent with the hypothesis that a diagnosis of SLE led to a more aggressive and targeted treatment, possibly improving patient outcome over time [17-19]. …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A higher percentage of cases than controls was treated with corticosteroids or anti-rheumatic medications (methotrexate and hydroxychloroquine), consistent with the hypothesis that a diagnosis of SLE led to a more aggressive and targeted treatment, possibly improving patient outcome over time [17-19]. …”
Section: Discussionsupporting
confidence: 64%
“…SLE is a frequent diagnosis (20-60%) in patients who evolve over time from undifferentiated CTD to a specific CTD [6], however it may take several years for a definitive diagnosis to be made [15, 16]. On the other hand, early diagnosis and targeted and timely therapy may prevent flares and late organ damage [17], improve quality of life [18], and decrease healthcare utilization and costs [19-21]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, a Danish cohort of 100 people with lupus nephritis followed for a median of 15 years found that delayed diagnosis and delayed intervention increased risk of progression to end-stage renal failure. (3) Furthermore a US health insurance database study found that diagnosis (defined as date of the first International Classification of Diseases (ICD)-9 code for SLE) delayed more than 6 months from symptom-onset (defined as the second diagnostic code for a symptom of SLE such as malar rash, photosensitivity, arthritis, 5 pleurisy or an ANA test in the 12 months prior to SLE diagnosis) lead to greater flare rates, healthcare utilisation and more insurance claims (4) suggesting that earlier diagnosis may enhance patient outcomes.…”
Section: It Is Not Clear Where Delays Between Symptom-onset and Sle Dmentioning
confidence: 99%
“…An alternative screening test such as a more specific or inexpensive biomarker for SLE during the period of non-specific symptoms and medical visits may enhance early detection. Previous studies have suggested that if diagnosis of SLE could be made earlier patient outcomes could be improved and healthcare costs reduced (3,4). It is hoped that tools such as this model may enable earlier diagnosis of individuals with clinical features suggestive of SLE.…”
Section: Model Validationmentioning
confidence: 99%
“…However, evidence from one tertiary care center suggests that only 60% of patients with SLE meet ACR criteria [5]; apparently, patients with early signs or limited disease are excluded by this tool. The development of improved diagnostic biomarkers facilitating the early detection of SLE is of utmost importance, not only because this would allow for rapid treatment and subsequent prevention of organ damage, but also because of the positive economic impact of early diagnosis [6]. …”
Section: Introductionmentioning
confidence: 99%